Joint Initiatives Instead of Multilateralism: A New Reality for the WTO? - O. V. Biryukova (Vestnik MGIMO-Universiteta)
The article examines the complexities of the negotiation function of the WTO, in which consensus in decision-making plays an important role. The author systematizes the possibilities and limitations for incorporating the results of plurilateral negotiations (i.e., with a limited number of participants) held within the framework of the so-called joint statement initiatives into the organization's law. The article also analyzes the prospects for integrating specific joint initiatives (internal regulation in services, simplification of investments in development, e-commerce) into the WTO system. The article emphasizes that despite standard features, all initiatives are unique in their content, format, and history and are at different stages of readiness, for Russia, which takes an active part in these joint initiatives, bringing the negotiations to a conclusion. The article criticizes joint initiatives from their primary opponents (India and South Africa), who insist that plurilateral initiatives' participation ignores existing multilateral mandates reached by consensus. Thus, they destroy the multilateral system.The purpose of the article is to review conceptual and practical approaches to forming new trade rules in the WTO system in the context of the multilateral crisis. The author concludes that plurilateral agreements can become a way out of the crisis in the negotiation function of the WTO, as well as the basis for future trade agreements in the system of organization. However, for plurilateralism to be effective and sustainable, it must be linked to multilateral norms and principles. Any plurilateral approach must allow flexibility in forming the basis for negotiating trade rules at multilateral level. It seems that if in the near future the WTO does not take decisive actions to adjust the rules and procedures for the new agreements, the prospects for advancing negotiations and maintaining the relevance of the leading institution of the international trading system will become even bleaker.